Cross Layer Routing Protocol in WSN - Performance analysis - S, Lokesh; BN, Yuvaraju (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) is a self-configuring network of small sensor nodes communicating among themselves using radio signals and deployed in quantity to sense, monitor and understand the physical condition. In this paper, much of interest is shown towards the design of WSNs by using cross layer Adaptive Dynamic Retransmission technique. The objective of the work is to compare the performance of the DSR (Dynamic Source Routing) and PSR (Proactive Source Routing) protocol with the proposed work. The DSR and PSR protocols consumes more energy, hence it is required to design an energy efficient routing protocol for WSN. The performance of above mentioned techniques is compared on basis of parameters such as Throughput, Packet Delivery Ratio, Packet Loss Ratio and End to End Delay. Mechanism of the proposed work is adapted to transmit power between two nodes and to utilize the transmitted energy efficiently by making use of adaptive Dynamic Retransmission technique.